Muscle hypertrophy in athlete training from a medical point of view - what do we know - Jan Biłogras; Katarzyna Kostelecka; Łukasz Bryliński; Marcin Wais; Dariusz Gruca; Konrad Warchoł (Journal of Education, Health and Sport, 2023)
Introduction